The Influence of Urbanization on Environmental, Economic, and Social Performance - Zidfina Aunal Hana; Amin Pujiati (Universitas Negeri Semarang, 2023)
The phenomenon of urbanization continues to increase in Indonesia. Urbanization can have both positive and negative influences. The higher urban population will push many industries, but environmental issues also potentially increase. On the other hand, more density leads to increased competition for work, which potentially increases crime. As a result, this study intends to investigate how urbanization affects Indonesia's environmental, economic, and social performance. The study employed a quantitative technique utilizing panel data from 33 Indonesian provinces for the years 2010, 2015, and 2020, which was then evaluated using the structural equation-partial least square model on SmartPLS 3.0. The findings revealed that urbanization had a significant negative effect on the environmental quality index. Meanwhile, urbanization had a significant positive effect on gross regional domestic product and the number of victims of theft. It can be concluded that urbanization encouraged economic improvement, but had the potential to worsen environmental conditions and crime. Thus, to reduce the negative impact on the environment, the government needs to emphasize the use of environmentally friendly fuels to the public. Also, implementing requirements for residents who will carry out urbanization to have skills that can be absorbed by the world of work